GREEN BANKING IN INDIA: PROBLEMS AND PROSPECTS - Sahoo, Bibhu Prasad; Singh, Amandeep; Jain, Neeraj (International Journal of Research -GRANTHAALAYAH, 2016)
Green banking is different from traditional banking, as green banking focus on promoting environment friendly banking. Green banking is also known as ethical banking. This paper attempts to analyze the adoption of green banking products among customers with different age groups. ANOVA and post hoc tests are applied for analyzing the objectives. This paper finding explains that there is significant difference in the usage of green banking products across various age groups individuals, as young generation is more inclined towards green banking products than middle age and senior age groups. Therefore, more awareness is need to be created among the middle and senior age groups individuals.